1996
DOI: 10.1021/tx9502150
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of in Vitro and in Vivo Exposure to Sulfur Mustard by GC/MS Determination of the N-Terminal Valine Adduct in Hemoglobin after a Modified Edman Degradation

Abstract: We report that exposure to the chemical warfare agent sulfur mustard can be monitored by means of a modified Edman degradation involving selective release of the N-terminal valine adduct of hemoglobin with the agent. The degree of alkylation of the N-terminal valine in human hemoglobin is approximately 1-2% of the total alkylation induced in hemoglobin upon treatment of human blood with sulfur mustard. After modified Edman degradation, followed by derivatization with heptafluorobutyric anhydride, the obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(37 citation statements)
references
References 14 publications
2
35
0
Order By: Relevance
“…A series of oxidation, hydrolysis or β-lyase-free metabolites and covalent adducts with macromolecules of SM have been identified in urine (Barr et al 2008;Black et al 1992b;Black and Read 1995;Davison et al 1961;Fidder et al 1996b;Read and Black 2004;Sandelowsky et al 1992;Zhang et al 2014) and blood Black et al 1997a, b;Fidder et al , 1996aNoort et al 1997;Sandelowsky et al 1992;van der Schans et al 1994) after SM exposure. The excretion or toxicokinetic profiles of these metabolites and adducts were studied to get an insight into the mechanism of toxicity and metabolism of SM.…”
Section: Introductionmentioning
confidence: 99%
“…A series of oxidation, hydrolysis or β-lyase-free metabolites and covalent adducts with macromolecules of SM have been identified in urine (Barr et al 2008;Black et al 1992b;Black and Read 1995;Davison et al 1961;Fidder et al 1996b;Read and Black 2004;Sandelowsky et al 1992;Zhang et al 2014) and blood Black et al 1997a, b;Fidder et al , 1996aNoort et al 1997;Sandelowsky et al 1992;van der Schans et al 1994) after SM exposure. The excretion or toxicokinetic profiles of these metabolites and adducts were studied to get an insight into the mechanism of toxicity and metabolism of SM.…”
Section: Introductionmentioning
confidence: 99%
“…The results are comparable to binding data obtained for haemoglobin, as determined previously. 9 The binding to both proteins is linear with the sulfur mustard concentration, whereas the percentage of sulfur mustard that is bound to the proteins is of the same order, i.e. 20% and 25% for albumin and haemoglobin, respectively.…”
Section: Detection Of Albumin Adductsmentioning
confidence: 97%
“…3 Within this framework we have worked on the development of immunochemical and mass spectrometric methods for diagnosis and dosimetry of exposure to sulfur mustard. [4][5][6][7][8][9][10][11][12] The present work concentrates on: the development of a standard operating procedure (SOP) for the gas chromatography/mass spectrometry (GC-NCI/MS) determination of sulfur mustard adducts to the N-terminal valine in haemoglobin in human blood by using the modified Edman degradation, and further exploratory research on adduct formation with the proteins albumin and keratin in order to develop suitable immunochemical and mass spectrometric methods for the detection of sulfur mustard adducts of these proteins. S188 D. NOORT ET AL.…”
Section: Introductionmentioning
confidence: 99%
“…Fidder et al have shown that mustard gas combines with the N-terminal valine residue of human hemoglobin, by detecting the mustard gasvaline adduct, using GC-MS under negative ionization after modified Edman degradation and heptafluorobutyric derivatization. 29) Other mustard gas adducts, cysteine, aspartic acid, glutamic acid and histidine adduct, have also been found for human hemoglobin. 30,31) Mustard gas has been shown to alkylate a cysteine residue in human serum albumin, and the alkylation site was identified in a tryptic digest of mustard-gas-exposed albumin.…”
Section: Analysis Of Mustard Gas and Nitrogen Mustard Adductsmentioning
confidence: 98%